Male intergenerational intimacy : historical, socio-psychological and legal perspectives - Sandfort, Theo; Brongersma, Edward; van Naerssens, Alex (New York : Harrington Park Press, 1991)
Fonds Suzan Daniel (FSD)ook uitgegeven als Journal of Homosexuality 20(1990) 1-2
0-918393-78-7
Engels
Monografie